Does the Morphology of the Forelimb Flexor Muscles Differ Between Lizards Using Different Habitats?. Issue 3 (8th February 2018) - Lowie, Aurélien; Herrel, Anthony; Abdala, Virginia; Manzano, Adriana S.; Fabre, Anne‐Claire
ABSTRACT: Lizards are an interesting group to study how habitat use impacts the morphology of the forelimb because they occupy a great diversity of ecological niches. In this study, we specifically investigated whether habitat use impacts the morphology of the forelimb flexor muscles in lizards. To do so, we performed dissections and quantified the physiological cross sectional area (PCSA), the fiber length, and the mass of four flexor muscles in 21 different species of lizards. Our results show that only the PCSA of the m . flexor carpi radialis is different among lizards with different ecologies (arboreal versus non‐arboreal). This difference disappeared, however, when taking phylogeny into account. Arboreal species have a higher m . flexor carpi radialis cross sectional area likely allowing them to flex the wrist more forcefully which may allow them climb and hold on to branches better. In contrast, other muscles are not different between arboreal and non‐arboreal species. Further studies focusing on additional anatomical features of the lizard forelimb as well as studies documenting how lizards use the arboreal niche are needed to fully understand how an arboreal life style may constrain limb morphology in lizards. Anat Rec, 301:424–433, 2018. © 2018 Wiley Periodicals, Inc.